Transformations of the Concept of Poetry among Muslim Philosophers in Light of Arabic Rhetoric: From Imitation to Imagination… and Change - katina, hecin (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(--header-height)" dir="auto" data-turn-id="37b7d45e-d938-4ccc-940c-1fec028a8882" data-testid="conversation-turn-119" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:a6b2ebb2-304a-48ab-8736-5ad337282e90-59" data-testid="conversation-turn-120" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="9788c804-5c22-4a4b-9c71-d5705f206660" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> If the Arabs’ engagement with Aristotelian philosophy falls within their broader effort to comprehend, interact with, and benefit from the knowledge of others, then their commentaries and summaries of its poetics pursued another objective: to achieve a comparative reading between Arabic poetics and Greek poetics. In the course of this reading, they encountered numerous precise terms and concepts whose scientific understanding and systematic comprehension required grasping the theoretical background on which they were based. Since this proved difficult—due to their lack of knowledge of theater and the absence of any theatrical practice in their immediate or distant geographic surroundings—the act of reading for them transformed into a foundational process. They effectively transplanted Aristotle’s terms and poetic concepts into the framework of classical Arabic rhetoric, which ultimately led to the incorporation of many authentic Arabic terms into Aristotelian poetics and their interpretation through it.